Slavery and the Catholic Church in the United States: historical studies - Endres, David J. (The Catholic University of America Press, 2023)
"The intertwining of U.S. Catholicism and race-based slavery is a painful aspect of the Church's history. Many scholars have shied away from this uncomfortable topic, but in recent years a cadre of historians have studied Catholics' varied roles: as enslaved persons, slaveholders, defenders of slavery, and, in a few cases, advocates of abolition and emancipation. This collection of nine essays is divided into three sections: enslaved persons and slaveholders, debating abolition and emancipation, and historians and historiography. The studies, many of which are informed by recent archival discoveries, offer a model for historians seeking to understand the relationship between slavery and the Church, not only topically but in terms of methods, contexts, and resources. They contribute to a broader appreciation of religion's role in race-based slavery and, in doing so, will assist scholars, teachers, and students in the contemporary discussion involving slavery, racism, and their legacies"--